2019
DOI: 10.2106/jbjs.18.01300
|View full text |Cite|
|
Sign up to set email alerts
|

Subtalar Arthrodesis with Use of Adipose-Derived Cellular Bone Matrix Compared with Autologous Bone Graft

Abstract: Update This article was updated on November 7, 2019, because of a previous error. On page 1909, in the section entitled “Discussion,” the sentence that had read “Radiographic nonunion rates of 69.2% and 45.6% were observed at 6 months for ACBM and autograft, respectively, as measured on CT scans; however, these nonunion rates do account for patients who were considered to have attained fusion according to traditional methods, including absence of pain and swelling and presence of arthrodesis on radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 35 publications
0
32
0
Order By: Relevance
“…Adipose-derived stem cells have also been used in the process of allograft preparation. The clinical utility of ASC allografts was tested in patients with subtalar joint arthritis as an alternative treatment to typical autologous bone graft in performed subtalar arthrodesis and both methods had similar efficacy in patients' quality of life enhancement [121,125]. Furthermore, it has been reported that the intradiscal injection of a mixture of ASCs and hyaluronic acid was safe for patients and could significantly reduce chronic discogenic low back pain [126].…”
Section: Human Clinical Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adipose-derived stem cells have also been used in the process of allograft preparation. The clinical utility of ASC allografts was tested in patients with subtalar joint arthritis as an alternative treatment to typical autologous bone graft in performed subtalar arthrodesis and both methods had similar efficacy in patients' quality of life enhancement [121,125]. Furthermore, it has been reported that the intradiscal injection of a mixture of ASCs and hyaluronic acid was safe for patients and could significantly reduce chronic discogenic low back pain [126].…”
Section: Human Clinical Trialsmentioning
confidence: 99%
“…Subtalar arthrodesis with use of adipose-derived cellular bone matrix compared with autologous bone graft: A multicenter, randomized controlled trial [125] Prospective, randomized, controlled trial…”
Section: Human Clinical Trialsmentioning
confidence: 99%
“…The FFI‐R was developed with patients who were predominantly middle‐aged (mean of 69 years) men with foot arthritis . The questionnaire has also been used as an outcome measure for surgical studies .…”
Section: Foot Function Index–revisedmentioning
confidence: 99%
“…The FFI‐R has been used as an outcome measure in clinical trials of medial knee osteoarthritis , first metatarsophalangeal joint osteoarthritis , plantar fasciitis , and diabetic foot ulcers and has been used to evaluate surgical implants .…”
Section: Foot Function Index–revisedmentioning
confidence: 99%
“…[1][2][3]5,9,14 Numerous studies have demonstrated the safety and efficacy of the use of nitinol compression staples in TMT fusion 3,9,13,14,16,23 and generally have fusion rates near 90%, comparable to literature rated for conventional fixation. 19 Although some clinical data exist regarding union rate using BME ELITE compression staples in TMT fusion, the data lack objective preoperative and postoperative data and analysis. In this report, validated clinical outcome scores were used to assess the subjective efficacy of midfoot arthrodesis using the new generation of nitinol staples.…”
Section: Introductionmentioning
confidence: 99%